TUGAS AKHIR EVALUASI TINGKAT KERUSAKAN JALAN SEBAGAI DASAR PENENTUAN PERBAIKAN JALAN MENGGUNAKAN METODE BINA MARGA DAN PAVEMENT CONDITION INDEX (PCI - , SALAKA BAYU P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The assessment of road surface condition is one step to determine the type of program that needs to be done revaluations. Two methods can be used in assessing the condition of the road is a method of Bina Marga and methods of PCI (Pavement Condition Index). This study aimed to evaluate and compare the condition of road Patuk and road Kramatan by both methods. The method used is a field of research with primary data in the form of road damage survey. The order of priority road handling with Bina Marga method is based on the value range of 0 to more than 7, while the method of pavement condition index PCI rank from 0 to 100. The results of the evaluation for both condition of roads for PCI method turns out to produce the same relative valuation, which is the condition of the roads are still in fair condition but in need of repair. As for the method of Bina Marga maintenance found differences both sides of the road, ie for periodic maintenance of roads Patuk use in priority order 4, while the Kramatan using periodic maintenance in order of priority 6.